Pengaruh Disiplin Belajar Dan Motivasi Belajar Terhadap Hasil Belajar Dengan Menggunakan Pembelajaran E-Learning Pada Sekolah Minggu Buddha (Smb) Chong De Se-Sumatera Utara - Sylvia Lestari; Muljadi; Lianah (Dhammavicaya : Jurnal Pengkajian Dhamma, 2022)
This research was conducted ƭ on ƭ the ƭ factorsƭ thatƭ affectƭ learning ƭ outcomes, ƭ especially ƭ on ƭ the ƭ subject ƭ of ƭ Buddhism at SMB Chong De, North Sumatra. Thisƭ research ƭ wasƭ initially ƭ motivatedƭ by ƭ theƭ fact ƭ thatƭ studentƭ learningƭ outcomesƭ varied and tended to be low. Based on the previous analysis, ƭ it ƭ shows ƭ that ƭ student ƭ learning ƭ outcomes ƭ are ƭ in ƭ line ƭ with ƭ habits ƭ that ƭ do ƭ not show discipline and motivation in learning ƭ when ƭ learning ƭ with ƭ e-learning, ƭ this ƭ is ƭ shown ƭ by ƭ the ƭ tasks ƭ done ƭ by ƭ plagiarizing ƭ from the internet. This research was conductedƭ usingƭ aƭ quantitativeƭ approachƭ withƭ exƭ postƭ factoƭ type.ƭ Theƭ respondentsƭ ofƭ thisƭ study were 336 students and 183 samples used in thisƭ studyƭ wereƭ determinedƭ basedƭ onƭ the ƭ Slovinƭ formula.ƭ Collectingƭ dataƭ usingƭ a ƭ questionnaire with a Likert scale of 4 choices. The validityƭ testƭ wasƭ carried ƭ outƭ with ƭ the ƭ Product ƭ Momentƭ Correlation ƭ andƭ the ƭ reliability was carried out with the Cronbach Alpha formulaƭ whileƭ theƭ homogeneityƭ testƭ wasƭ carriedƭ outƭ withƭ theƭ Bartletƭ test.ƭ Theƭ resultsƭ showed that (1) there was a positive influence of ƭ discipline ƭ with ƭ learning ƭ outcomesƭ indicated ƭ by ƭ the ƭ correlationƭ coefficient ƭ of ƭ 0.895; (2) there is a positive effect of motivation withƭ learningƭ outcomesƭ indicatedƭ byƭ theƭ correlationƭ coefficientƭ ofƭ 0.899;ƭ (3)ƭ thereƭ isƭ an influence of discipline and motivation with learningƭ outcomesƭ together,ƭ indicatedƭ byƭ theƭ correlationƭ coefficientƭ valueƭ ofƭ 0.898